VD_FINDINFO HC / 2011 / 174 vom 4. April 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, RELATIONS PERSONNELLES | 176 al. 1 ch. 1 CC, 176 al. 3 CC, 273 CC, 308 al. 1 let. b CPC (CH)